ЕВОЛЮЦІЯ ІНТЕЛЕКТУАЛЬНИХ ЕЛЕКТРИЧНИХ МЕРЕЖ ТА ЇХНІ ПЕРСПЕКТИВИ В УКРАЇНІ - Стогній, Б.С.; Кириленко, О.В.; Праховник, А.В.; Денисюк, С.П. (Інститут електродинаміки НАН України, Київ, 2012)
Modern trends in global energy and form the basis of "electric world". The main provisions of the modern concept of Smart Grid, the features of the concept of "reasonable efficiency" and policies to implement Smart Grid concept in leading countries. Features of the evolution of smart grids, advanced forms and directions of development of Smart Grid technologies and their implementation in Ukraine. References 22, tables 3.